OPTIMALISASI KINERJA PEGAWAI SEKRETARIAT DEWAN PERWAKILAN RAKYAT DALAM MENDUKUNG AKUNTABILITAS ANGGARAN DPRD KABUPATEN SIKKA - Agnes Obeyane Longge; Yustina Olivia da Silva; Margaretha Yulianti (Universitas Nusa Nipa Maumere, 2026)
This internship report aimed to describe the results of the analysis of employee performance at the Secretariat of the DPRD of Sikka Regency, particularly in providing administrative support for the budgeting function and achieving organizational accountability. The internship was conducted for four months, from August 11 to December 12, 2025, and took place in the Budgeting and Oversight Division. Data collection methods used in preparing this report included participatory observation of bureaucratic activities, structured interviews with the Head of the Budgeting and Oversight Division, and review of internal documents such as the 2024 Performance Report (LAKIP). The analysis focused on identifying operational obstacles and formulating effective problem-solving strategies.The results of the analysis showed that although administrative governance had generally been implemented in accordance with procedures, significant constraints were still found, including limited human resource competencies, low levels of work discipline, and inadequate facilities and infrastructure. These issues affected delays in the completion of financial accountability reports (LPJ), which in turn influenced the credibility of budget accountability. As a solution, this report formulated optimization strategies through strengthening periodic technical guidance (Bimtek), increasing staff supervision, and improving the effectiveness of internal communication patterns. The implementation of these strategies is expected to ensure the creation of work efficiency and sustainable budget accountability within the Secretariat of the DPRD of Sikka Regency.